Species of Chinese materia medica resources based on the fourth national survey of Chinese materia medica resources - Luqi Huang; Lanping Guo; Xiaobo Zhang; Liying Yu; Jiahui Sun (Science of Traditional Chinese Medicine)
Abstract. This article outlines the composition and species characteristics of Chinese materia medica (CMM) resources identified in the fourth national survey of CMM resources. The survey was conducted based on field investigations and office collation, adhering to the “four principles” emphasizing the existence of survey records, voucher specimens, actual photographs, and evidence of medicinal use, to summarize the species of CMM resources and ensure the scientific integrity and accuracy of the results. According to the findings, China has 18,817 CMM resources, including 15,321 medicinal plants, 826 medicinal fungi, 2517 medicinal animals, and 153 medicinal minerals. Additionally, in the fourth national survey of CMM resources, 3151 species of unique medicinal plants, 464 species of rare and endangered medicinal plants, and 196 new species in China underwent specialized investigations. These latest statistics are expected to provide the most up-to-date foundational data for the protection, management, development, and utilization of these CMM resources over an extended period, offering scientific guidance for the development of the traditional Chinese medicine industry.